Systematic Literature Review Analysis: Effectiveness of Family Planning Programs in Reducing Maternal and Child Mortality Rates - Eugenia Carvalho de Araújo; Maria Jose Canossa Alves; Ana Claudia da Costa Guterres; Maria Cardoso dos Santos; Hercio Marta Fátima Ximenes (Journal of International Multidisciplinary Research, 2024)
The Family Planning program has long been known as an important intervention in efforts to reduce maternal and child mortality rates. This research aims to analyze the effectiveness of the Family Planning Program in reducing maternal and child mortality rates using the Systematic Literature Review (SLR) method. This research uses the SLR method by collecting and analyzing literature from various academic databases. Inclusion criteria included studies evaluating the impact of Family Planning programs on maternal and child mortality rates, published between 2019 and 2024. The literature selection process was carried out in two stages: initial screening and quality assessment using PRISMA guidelines. A total of 15 studies met the inclusion criteria and were analyzed in this study. The findings show that the Family Planning Program is effective in reducing maternal mortality through increasing access to reproductive health services, health education, and use of contraception. Apart from that, the Family Planning program is also effective in reducing child mortality by improving maternal health and preventing unwanted pregnancies. Challenges identified include limited access to health services in remote areas, cultural barriers, and lack of policy support. Family Planning programs have proven effective in reducing maternal and child mortality rates. To increase its effectiveness, it is necessary to increase accessibility, service quality, and adequate policy support. It is hoped that these recommendations will help in improving the implementation of Family Planning programs and maternal and child health policies in the future.